2011
DOI: 10.1530/joe-11-0254
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin is a novel regulator of osteoclast differentiation and function through inhibition of a canonical transient receptor potential 1-like cation channel

Abstract: This study investigated the role of urocortin (UCN), a member of the corticotrophin-releasing factor (CRF) family of peptides, in osteoclast maturation and function. We found that 10 K7 M UCN significantly (P!0 . 05) suppressed osteoclast differentiation from bone marrow precursor cells in culture and reduced the expression of several osteoclastic markers. Furthermore, UCN potently suppressed osteoclast bone resorption, by significantly inhibiting both the plan area of bone resorbed by osteoclasts and actin ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 58 publications
0
27
0
1
Order By: Relevance
“…33 One study showed that MSCC blocker gadolinium (Gd 3+ ) could inhibit actin ring formation in osteoclasts, whereas modulators of voltage-dependent Ca 2+ channels had no effect. 5 Another source of [Ca 2+ ] i in osteoclasts is internal stores such as endoplasmic reticulum (ER). The extracellular stimuli like calcium ion or ATP activate the plasma membrane receptors, which further induces the phospholipase C (PLC) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…33 One study showed that MSCC blocker gadolinium (Gd 3+ ) could inhibit actin ring formation in osteoclasts, whereas modulators of voltage-dependent Ca 2+ channels had no effect. 5 Another source of [Ca 2+ ] i in osteoclasts is internal stores such as endoplasmic reticulum (ER). The extracellular stimuli like calcium ion or ATP activate the plasma membrane receptors, which further induces the phospholipase C (PLC) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As with all studies involving cell lines, these observations should, and will be, confirmed in primary chondrocytes but these two characteristics ultimately represent a putative role for the Ucn system in preserving cartilage tissue. Furthermore, when coupled with our recently published data demonstrating a potent anti-resorbtive role for Ucn in osteoclasts, 19 a wider role in bone metabolism and maintenance is suggested. Together, these data would suggest that Ucn, by preserving the ability to lay down new cartilage as well as reducing bone resorption, may have therapeutic potential in both osteoporosis and OA.…”
Section: Discussionmentioning
confidence: 57%
“…This small peptide and its paralogs UcnII (human stresscopin-related peptide) and UcnIII (human stresscopin) are members of the corticotrophin releasing factor (CRF) family. These peptides have been demonstrated to have pleiotrophic effects on numerous cell systems including anti-apoptotic actions in heart 18 and the regulation of skeletal osteoclast differentiation and resorption, 19 acting in an autocrine or paracrine manner. 20 These agonists bind to two classes of receptor CRF receptor 1 (CRFR1) and CRFR2 (which are expressed as multiple isoforms due to alternate RNA splicing 21 ).…”
mentioning
confidence: 99%
“…These peptides are evolutionary ancient molecules having representatives in lower vertebrates such as sauvagine and urotensin, found in amphibia and fish respectively 15, 16 . Although originally found in the brain, Ucn1 has now been found in many peripheral tissues where it exerts diverse effects including: cardioprotection 17 , antiresorptive activity in bone 18 and control of the myometrium at term 19 . Two further paralogues of Ucn1 have also been isolated; Ucn2 (Human Stresscopin Related Peptide), and Ucn3 (Human Stresscopin), which are composed of 38 and 39 amino acids respectively 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the cardioprotective effect of Ucn1 involves a diverse range of ion channels including the inhibition of L-type calcium channels 26 but also to increase KATP channel gene expression and activation 17, 27 . Furthermore, in the male reproductive system, the reported regulation of spermatogenesis by Ucn1 has been demonstrated to involve T-type Ca 2+ channels 28 , whereas the osteoclast inhibitory effect of Ucn1 involves regulation of Ca 2+ ions by inhibition of a TRPC1-like cation current 18 .…”
Section: Introductionmentioning
confidence: 99%